2017
DOI: 10.1111/cfs.12371
|View full text |Cite
|
Sign up to set email alerts
|

“It's better than it used to be”: Perspectives of adolescent siblings of children with an autism spectrum condition

Abstract: This article reports on the lived experiences of 11 adolescents who have a brother or a sister with a diagnosis of autism spectrum condition. Through semistructured, in‐depth, in‐person interviews, these adolescents shared their experiences and perceptions. These exploratory findings can be used to inform the practice of social workers and other health professionals, and future research. Implications for practice focus on the importance of exploring experiences and perceptions of siblings of children diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
2
37
1
3
Order By: Relevance
“…This is in contrast to our current study, which indicates that sisters are successful in their care taking roles despite the complex needs of their autistic siblings and described themselves as "kind guardians", "feeling connected", "showing compassion", "proud of offering help" and consider that they show effective problem solving during everyday routines (see also, Chan & Goh, 2014). Gorjy et al (2017) also confirm the great capacity of their adolescent participant siblings for deep feelings of love, empathy tolerance and acceptance of the autistic identity of their siblings. In addition, our results show that the struggle during caretaking activities arises mostly when sisters have to balance parental expectations (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to our current study, which indicates that sisters are successful in their care taking roles despite the complex needs of their autistic siblings and described themselves as "kind guardians", "feeling connected", "showing compassion", "proud of offering help" and consider that they show effective problem solving during everyday routines (see also, Chan & Goh, 2014). Gorjy et al (2017) also confirm the great capacity of their adolescent participant siblings for deep feelings of love, empathy tolerance and acceptance of the autistic identity of their siblings. In addition, our results show that the struggle during caretaking activities arises mostly when sisters have to balance parental expectations (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with the lifeworld framework we proposed, this study drew our attention to sisters' humanising dimensionssuch as the need to feeling respected, secure, valued, involved and informed -in the data presented above. With this study, we echo Gorjy et al (2017) who acknowledge explicitly the strengths, abilities and resourcefulness of teenage TD siblings. This study found an equal number of the possible struggles and opportunities for growth in the life of sisters of an autistic child as shown above in Table 5.…”
Section: An Existential View Of Wellbeing: Agency and Vulnerability Amentioning
confidence: 61%
“…There have been further encouraging developments in autism sibling research, including research that e x a m i n e s siblings' experiences directly using semi-structured qualitative interviews from a strengths-based approach (Gorjy, Fielding & Falkmer , 2017) and photo elicitation interviews (Latta et al, 2014). While researchers posed questions using siblings' photos to encourage children to talk freely and explain more about their experiences, siblings were not actively involved in any stage of the research other than discussing their photos with the researcher.…”
Section: Methodological Considerations Of Past Research and The Need For Collaborative Researchmentioning
confidence: 99%
“…Oni koriste niz obrambenih mehanizama kako bi se prilagodili tim negativnim iskustvima. To uključuje odvraćanje pažnje, rješavanje problema, rezignaciju, emocionalnu kontrolu i pomicanje osobnih granica te izolaciju 10 je za prihvaćanje autističnog brata ili sestre najvažnije suočavanje s novonastalom situacijom. Imati člana obitelji s autizmom ne mora biti nužno negativno iskustvo.…”
Section: Utjecaj žIvota S Autističnim Djetetom Na Braću I Sestreunclassified
“…Prevalencija poremećaja iz autističnog spektra porasla je uslijed novih dija-rivanje partnera i problemi u odnosu zbog preokupacije bolesnim djetetom 8,9 . U takvoj obiteljskoj zajednici negativne emocije doživljavaju i ostali članovi, naročito braća i sestre djeteta s autizmom 10 . Pristup djetetu s ASD-om treba biti multidisciplinaran, što podrazumijeva suradnju brojnih stručnjaka iz različitih područja medicine.…”
unclassified